2021
DOI: 10.26529/cepsj.1032
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Mediating Role of Altruism in the Relationship between Empathic Tendencies, the Nature Relatedness, and Environmental Consciousness

Abstract: A study was conducted using a correlational screening model to determine the mediating effect of altruism in the relationship between empathic tendencies, the nature relatedness and environmental consciousness. The participants of the study, selected via random cluster sampling design, are composed of 305 pre-school teachers working in pre-schools and kindergartens in a city located in Turkey’s Aegean region. The ‘Empathic Tendency Scale’, ‘Altruism Scale’, ‘Nature Relatedness Scale’, and ‘Environmental Consci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…One of them is the lack of knowledge about environmental content among teachers and the lack of time to prepare for teaching environmental content. Other obstacles include lack of training or opportunities for continuous professional development, lack of technical support, safety concerns, responsibility for teaching outside the classroom, lack of financial resources, lack of interest and support from local partners, and lack of support from parents (Rebolj & Devetak, 2012;Yurtsever & Angın, 2022).…”
Section: Environmental Contents In Science Textbooks and Science Curr...mentioning
confidence: 99%
“…One of them is the lack of knowledge about environmental content among teachers and the lack of time to prepare for teaching environmental content. Other obstacles include lack of training or opportunities for continuous professional development, lack of technical support, safety concerns, responsibility for teaching outside the classroom, lack of financial resources, lack of interest and support from local partners, and lack of support from parents (Rebolj & Devetak, 2012;Yurtsever & Angın, 2022).…”
Section: Environmental Contents In Science Textbooks and Science Curr...mentioning
confidence: 99%
“…Nature-relatedness is a psychological construct that explains the subjective relationship between the natural environment and individuals, encompassing cognitive, emotional, and experiential aspects of individuals’ interaction with nature ( Huang et al, 2022 ). It is characterized by feelings of gratitude, understanding, and commitment to the natural world ( Sadowski et al, 2022 ), emphasizing the recognition of oneself as a part of nature and feeling responsible for other living things and the environment ( Yurtsever and Angın, 2021 ). Research has shown that individuals with a higher connection to nature are more concerned about environmental issues and more likely to engage in eco-friendly behaviors, considering the impact of their actions on the environment ( Wilkie, 2019 ; DeVille et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%